Professional learning community via virtual among teachers promotes the teaching quality of 21st century learning in Malaysia during the covid-19 pandemic: a conceptual review - Gurumoorthy Poobalan; Roslee Talip (Pusat Penataran Ilmu Bahasa, Universiti Malaysia Sabah, 2020)
Corona Virus Disease 2019 (COVID-19) in Malaysia since early of 2020 has transferred traditional face-to-face teaching to online education platforms, which directly affects the quality of education. This concept paper discusses and purpose the practice of professional learning community via virtual among teachers promotes the quality of 21st Century Learning in Malaysia during the pandemic of COVID-19. School leaders, teachers and Non-government community play an important role in achieving educational transformation. Therefore, the development of teaching quality should grow in line school transformation with 3rd wave of the Malaysia Education Blueprint (2021-2025). Researchers uncover professional learning community practices in helping teachers improve the quality of teaching through lesson study, peer coaching, and teacher sharing session by virtual. To find the information needed, the researcher used a library study. Based on findings, virtual academic coaching and sharing collaboration approaches in education through a professional learning community among teachers has helped to enhance the quality of teaching to increase the excel of students during the covid-19 pandemic. Researcher suggests few online platform medium to strengthen teaching quality of 21st Century Learning. The findings of the study will fill the gaps in future literature review of professional learning community practices among teachers.